2016
DOI: 10.1177/1078087416669059
|View full text |Cite
|
Sign up to set email alerts
|

Do Residents of Low-Income Communities Trust Organizations to Speak on Their Behalf? Differences by Organizational Type

Abstract: Low-income people of color in urban communities have been found to suffer from high levels of political inequality and poor political representation. To make policy more responsive and accountable, neighborhood organizations are often solicited to serve as informal community representatives in local decision-making processes. Given this reliance on nonelected representatives, we ask, Do community residents believe neighborhood organizations are legitimate representatives of their interests? Using survey data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Policy can work through organizations to help them do so. Research shows that policy‐favored nonprofits function as nonelected representatives of disadvantaged communities in local politics and public affairs (Berry & Arons, ; Levine, ) and low‐income citizens view them as good and legitimate representatives of their interests (Mosley & Grogan, ; Park, Mosley, & Grogan, ).…”
Section: Affecting Political Visibilitymentioning
confidence: 99%
“…Policy can work through organizations to help them do so. Research shows that policy‐favored nonprofits function as nonelected representatives of disadvantaged communities in local politics and public affairs (Berry & Arons, ; Levine, ) and low‐income citizens view them as good and legitimate representatives of their interests (Mosley & Grogan, ; Park, Mosley, & Grogan, ).…”
Section: Affecting Political Visibilitymentioning
confidence: 99%
“…At the same time, unbalanced attention toward one area of organizational scholarship is a concerning trend. Human service organizations have been considered as venues for not just health and social service provision, but civic engagement, empowerment, community organizing, and social change (Hasenfeld & Garrow, 2012;Park, Mosley, & Grogan, 2016). Organizational studies simply facilitating and fueling service implementation and de-implementation can harm the overall missions of the social work profession and scholarship.…”
Section: Implications and Recommendationsmentioning
confidence: 99%
“…In the area of nonprofit scholarship, a host of scholars have provided evidence that particular nonprofits (CBOs) are uniquely positioned to represent communities, enable civic participation, and foster democratic governance (Alexander, 2011; Chaskin & Greenberg, 2013; LeRoux, 2007; Mosley & Grogan, 2013; Park, Mosley, & Grogan, 2018). CBOs are defined as public or private nonprofit organizations that are representative of a community or significant segments of the community and provide educational or related services to individuals in the community (20 USCS § 7801(6)).…”
Section: Literature Review: From Citizen Participation To Civic Healthmentioning
confidence: 99%
“…CBOs are defined as public or private nonprofit organizations that are representative of a community or significant segments of the community and provide educational or related services to individuals in the community (20 USCS § 7801(6)). These organizations were identified as indispensable structures for providing citizens with a voice in community decisions, and particularly for counteracting the representational challenges of marginalized communities (Mosley & Grogan, 2013; Park et al, 2018). For example, a 10-year longitudinal study of a county human service agency’s partnerships with CBOs revealed that neighborhood organizations “fostered the generation of democratic knowledge that informed administrative decision making” and enhanced the public organization’s accountability to marginalized citizens (Alexander, 2011, p. 114).…”
Section: Literature Review: From Citizen Participation To Civic Healthmentioning
confidence: 99%
See 1 more Smart Citation